PERILAKU TOXIC DALAM KOMUNIKASI VIRTUAL DI GAME ONLINE MOBILE LEGENDS: BANG BANG PADA MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK DI UNIVERSITAS MUHAMMADIYAH PALANGKARAYA: Toxic Behavior in Virtual Communication Onmobile Legends: Bang Bang Online Game in Students of the Faculty of Social And Political Sciences at Muhammadiyah Palangkaraya University - Regina Wynalda Abie; Srie Rosmilawati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Gadgets has become everyone's daily needs, apart from being a communication tool and looking for an information, gadgets are also a tool for seeking entertainment, one of which is playing offline and online games. There are lots of people from children to adults who play online games, one of which is Mobile Legends: Bang Bang, a game that provides this chatting feature is often misused by many people to spread hate during the game, this is called to be toxic behavior. This study uses qualitative research which includes the process of observation, interviews, and documentation targeting students of the Faculty of Social and Political Sciences. This research proves that the phenomenon of toxic behavior occurs when a teammate plays badly and also when a teammate blames one another. This makes emotions unstable and performs toxic behavior in the form of speaking harsh words. In addition, based on the results of research, FISIP students have the characteristics of inconsistency and like to make conflicts during games.